Green synthesis of superparamagnetic iron oxide nanoparticles with eucalyptus globulus extract and their application in the removal of heavy metals from agricultural soil - Andrade Zavaleta, Karin (2022)
The green synthesis of metal oxide nanoparticles is presented as an excellent sustainable alternative for achieving nanostructures, with potential applications. This research provides important information regarding the inﬂuence of the type of solvent used in extracting organic reducing agents from E.globulus on the FeO NPs green synthesis protocol. A broad approach to characterization is presented, where UV-vis spectrophotometry suggests the presence of this type of nanoparticulate material. Likewise, the reduction mechanism was evaluated by FT-IR and the magnetic properties were evaluated by PPSM. In addition, characterizations were linked via elemental analysis (EDX), crystallographic characterization (XRD), electron microscopy (SEM/STEM), and Z potential to evaluate colloidal stability. The results show the inﬂuence of the type of solvent used for the extraction of organic reducing agents from E.globulus, and the effect on the synthesis of FeO NPs. In addition, the nanostructure material obtained showed excellent efﬁciency in the remediation of agricultural soil, eliminating metals such as Cr-VI, Cd, and, to a lesser extent, Pb.